Postnatal Development of Microglia-Like Cells in Mouse Cochlea - Penghui Chen; Yongchuan Chai; Haijin Liu; Gen Li; Longhao Wang; Tao Yang; Hao Wu (Neural Plasticity, 2018)
Microglial cells are involved in surveillance and cleaning of the central nervous system. Recently, microglial-like cells (MLC) have been found in an adult cochlea and investigated for their role in cochlear inflammation. The presence and potential roles of MLCs during the development of the cochlea, however, remain unclear. In this study, immunostaining was performed using the MLC-specific marker IBA1 to characterize the presence, distribution, and morphology of MLCs in the developing cochlea. From P0 to P14, MLCs were present in a variety of cochlear regions including the modiolus, spiral lamina, spiral ganglion, spiral ligament, and the organ of Corti. Interestingly, the overall number of MLCs in a mouse cochlea steadily increased since P0, peaks at P5, then gradually decreased from P5 to P14. In the spiral ligament, the distribution of the MLCs trends to shift from the type I/II fibrocyte-rich regions to the type III/IV fibrocyte-rich regions during the course of cochlear development, accompanied by the morphological changes of MLCs from the amoeboid, activated form to the ramified, quiescent form. Our results suggested that MLCs experience drastic morphological and distributional changes during postnatal cochlear development, which may play a role in the maturing and remodeling of the cochlea.